Law as Strategy: The Weaponization of Trade Dispute Mechanisms in Sino-Western Relations - Rafiqi, Fathan; Maksum, Ali (Hasanuddin Journal of International Affairs, 2026)
This article investigates the transformation of international trade law into a strategic instrument of geopolitical contestation, focusing on the legal rivalry between China and Western countries. Employing Lawfare Theory and Legal Realism, the study adopts an interdisciplinary method combining legal doctrine, international relations theories, and empirical case studies from WTO and ISDS mechanisms. The findings reveal that legal platforms originally designed for neutral dispute resolution have been repurposed as tools of statecraft. China’s increased legal engagement post-2018 signals a shift toward strategic legalism, where litigation serves as foreign policy. Meanwhile, the United States exercises unilateral legal strategies, undermining multilateral institutions. These actions reflect a broader erosion of legal neutrality, leading to procedural asymmetries that disadvantage Global South countries. The article concludes that without institutional reform and renewed global commitment to procedural justice, international legal mechanisms risk becoming arenas of symbolic dominance rather than fair adjudication. This trend challenges the foundational purpose of international law as a stabilizing force and invites critical reevaluation of legal norms amid a multipolar world order.